Migration Trends of Foreign Employment in Beldandi Rural Municipality, Kanchanpur, Nepal (AMC Journal (Dhangadhi), 2025)
This research study explores migration trends of foreign employment in Beldandi Rural Municipality, Kanchanpur, Nepal, focusing on the socio-economic impacts of labor migration. It assesses the current migration status, factors driving the trend, and how financial incentives, family obligations, and personal goals influence decisions to work abroad. The research also evaluates household-level changes in income, living standards, and family dynamics. A sample of 308 migrants was selected from a population of 1,543 using Raosoft’s calculator, maintaining a 5% margin of error and 95% confidence level.Findings show 76.3% of migrants are male, with 46.8% aged 25–34. Most are from Brahmin/Chettri groups (58.1%) and follow Hinduism (79.9%). Secondary education is the highest level for 64.6% of respondents. India (37.0%), Malaysia (21.8%), and the UAE (13.3%) are the top destinations. Unemployment (43.5%) and poverty (36.0%) are the main push factors, while job availability (44.5%) and better wages (37.0%) act as pull factors.Around 37.3% earn less than NPR 25,000 per month. Remittances are mostly sent via IME (48.7%) and banks (39.9%) and used for daily expenses (36.7%) and home building (24.0%). Benefits include increased income (59.7%) and career growth (20.5%), though 65.6% face legal or visa issues, and only 30.8% received skill training.Foreign employment has enhanced financial stability (91.9%), family relationships (69.2%), and cultural identity (67.9%). The study calls for skill training, inclusive policies, regulated migration, and effective remittance use to ensure sustainable socio-economic development.